DESIGN AND f-ABRIC AT! ON OF A SURFACE pH SENSOR FOR A REALTIME CORROSION MONITORING - KAKOOEI, SAEID (2013)
The aim of this research is to design and fabricate a new pi I sensor that can be used to measure hydrogen ion activity on corroding metal surface in bulk solution or under deposit. Iridium oxide (lrOx) is used for proposed design as pH sensitive material. IrOx is a potentiometric sensor which its open circuit potential regarding a reference electrode is representative of pi I. The electrodcposition method of cyclic voltammetry approach is used for coating of IrOx on stainless steel substrate. The effects of scan rate. temperature. and number of cycles on the coating thickness of IrOx elcctrodeposited on a stainless steel substrate v.cre investigated in a statistical system. The central composite design. combined with response surface methodology, was used to study condition of electrodeposition.